THE EFFORTS OF IN ISLAMIC RELIGIOUS EDUCATION TEACHERS OVERCOME STUDENT DETERMINATION PROBLEMS AT JUNIOR HIGH SCHOOL - Yuliastutik, Rami (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Student delinquency is a classic problem that always appears in society. This problem is a very interesting and actual thing to discuss. Because the problem of student delinquency is a problem that affects the younger generation as happened at SMPI Miftahul Ulum Opo-Opo. To obtain data in this study, researchers used several methods, namely: interviews, observation, documentation and open questionnaires (and the questionnaires here are only a complement or extra). The collected data were analyzed using qualitative descriptive analysis. The conclusion of this study, which describes the forms of student delinquency at SMPI Miftahul Ulum Opo-Opo, is included in the category of mild delinquency, such as: skipping or not attending school without permission, not wearing school uniforms, making noise in class or outside class, not do homework. The efforts of Islamic Religious Education Teachers in treating student delinquency at SMPI Miftahul Ulum Opo-Opo are in a preventive way, including: emphasizing religious activities, pasting slogans in each class, establishing cooperation between schools and parents. And curative (healing) efforts, by giving special attention to students with problems, and emphasizing moral development for students.